2021
DOI: 10.1055/a-1674-0259
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Cancer-Associated Thrombosis

Abstract: Active malignancy increases the risk of developing venous thromboembolism (VTE) by four- to seven-fold. The risk of VTE, including deep vein thrombosis and pulmonary embolism, in patients with cancer varies based on several clinical factors, such as cancer stage and age. However, race and ethnicity are also associated with increased VTE risk. Black (African American) patients with cancer have a higher risk of developing VTE than White patients, while Asian/Pacific Islanders have a lower risk. Studies on cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
(43 reference statements)
1
11
0
Order By: Relevance
“…This difference underlines the relevance of estimating the occurrence of VTE events in different populations since ethnic variation can alter the rate of this outcome. Previous studies have described that cancer patients of Hispanic background are at higher risk of mortality due to pulmonary embolism in comparison with White individuals [12][13][14]; however, these analyses have also reported that Hispanic patients have lower rates of VTE than White and Caucasian populations. These contradictory results can be explained by several reasons.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This difference underlines the relevance of estimating the occurrence of VTE events in different populations since ethnic variation can alter the rate of this outcome. Previous studies have described that cancer patients of Hispanic background are at higher risk of mortality due to pulmonary embolism in comparison with White individuals [12][13][14]; however, these analyses have also reported that Hispanic patients have lower rates of VTE than White and Caucasian populations. These contradictory results can be explained by several reasons.…”
Section: Discussionmentioning
confidence: 91%
“…Although the KRS has been validated in several populations [5,[9][10][11], we found scarce data regarding the prognostic value of this tool among Hispanic patients from Latin American countries. Indeed, previous studies have described that Hispanic patients have a higher incidence of VTE in comparison to non-Hispanic Whites and Asian individuals, but a lower frequency of VTE in comparison to African American patients [12][13][14]. Moreover, recent studies have associated the KRS as a prognostic variable for overall survival (OS) in cancer patients, but most of these analyses have been carried out in different populations other than Hispanics [3].…”
Section: Introductionmentioning
confidence: 99%
“…We found that there is an increased risk of VTE in blacks and Hispanics compared to whites. This may be attributed to socioeconomic factors, access to healthcare, and racial disparities, such as blacks being less likely to receive direct oral anticoagulants [ 10 ]. Although blacks have a lower prevalence of factor V Leiden and other coagulation disorders compared to whites, they still maintain a higher risk.…”
Section: Discussionmentioning
confidence: 99%
“…In Asian patients with cancer, there are few prospective studies on risk factors for, and an RPM of, CAT occurrence (12)(13)(14). Although the risk of CAT is lower in Asian people than in other ethnic groups (15)(16)(17), VTE risk is much higher than usual in patients with metastatic cancer who are receiving chemotherapy, and VTE is one of the major causes of death among them (14,18). The occurrence of VTE can also interrupt or delay essential treatment, worsen quality of life, and increase the use of health care resources, including Usefulness of blood biomarkers for predicting venous thromboembolism in Japanese patients with cancer hospitalization (19).…”
Section: Introductionmentioning
confidence: 99%